1970
DOI: 10.2118/2579-pa
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acoustic Velocities for Natural Gas

Abstract: An equation of state based on the well known eight- Acoustic velocities for natural gas are calculated as a junction of temperature, pressure, and gas gravity. The method is based on a generalized equation of state for natural gas that may also be used to calculate a number of thermodynamic properties such as specific internal energy and isentropic expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It can be derived from energy balance around a stationary wave undergoing an infinitesimal perturbation [34,35]:…”
Section: Acoustic Velocity In Annulusmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be derived from energy balance around a stationary wave undergoing an infinitesimal perturbation [34,35]:…”
Section: Acoustic Velocity In Annulusmentioning
confidence: 99%
“…The acoustic velocity in annulus is mainly related to the composition, temperature and pressure of the annulus. It can be derived from energy balance around a stationary wave undergoing an infinitesimal perturbation [34,35]:…”
Section: Modeling Of Annulus Temperaturementioning
confidence: 99%
“…To make the calculation of the properties of mixtures more systematic, Batzle and Wang normalized pressure and temperature by the pseudocritical values, which are the weighted molar average of the pure compounds. Thomas et al (1970) found a relation to calculate these then called pseudoreduced values by the gravity G of the gas composition.…”
Section: Appendix a Comparison Of Equations Of Statementioning
confidence: 99%
“…But for pure methane Batzle and Wang found differences of several percent between calculated and measured velocities, which result from errors in the calculation of the volume in the BWR equation by Thomas et al (1970). Setzman and Wagner went a very different way.…”
Section: Appendix a Comparison Of Equations Of Statementioning
confidence: 99%
“…The LCF corrects the liquid density to account for the effect of the gas phase. In modern terms, the LCF is related to liquid holdup, H L , by: (1) and the F y term is simply (v SG ) sc /P 0.4 . Apparently the P 0.4 term is used to approximately convert standard condition gas flow rate to in-situ conditions, thereby approximating v SG .…”
Section: Introductionmentioning
confidence: 99%